2021
DOI: 10.1088/1742-6596/2063/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of phenolic compounds from Iraqi Coriandrum Sativum L. and loaded on copolymeric hydrogels and examine there as drug delivery system and antioxidant

Abstract: The phenolic extracts for leaves and stems (L+S) parts and leaves (L) part of Iraqi Coriandrum Sativum L. and their total phenols, total tannins and total flavonoids are described. Three copolymeric hydrogels prepared and loaded with phenolic extract 4 (U1-U3). The HPLC results show three phenolic compounds, while the GC-Mass results show one phenolic compound and four non-phenolic compounds. Gained results showed that there are significant (P < 0.05) variations in total phenols (9.822 ± 0.634−4.015 ± 0.118… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This value is almost 25 2021). The result of this study, the ethanolic extracts of the leaves and leaves with steam were more potent than the ethanolic extracts of the leaves alone, the ethanolic extracts of the leaves with steam, and the methanolic extracts (35).…”
Section: Total Phenolic Contents (Tpc) Amomum Subulatummentioning
confidence: 71%
“…This value is almost 25 2021). The result of this study, the ethanolic extracts of the leaves and leaves with steam were more potent than the ethanolic extracts of the leaves alone, the ethanolic extracts of the leaves with steam, and the methanolic extracts (35).…”
Section: Total Phenolic Contents (Tpc) Amomum Subulatummentioning
confidence: 71%
“…Regarding these results, coriander flavonoids are much higher than those reported by (Msaada et al, 2017) who observed that the flavonoid contents in Syria and Egypt were 2.51 and 2.07 mg QE/gDw, respectively. In Iraq, (Sadoun et al, 2021) analyzed the flavonoid contents of the ethanolic extract of coriander which was ranged from 3.422 to 8.112 mg QE/g DW. This value is close to the present obtained results, while the methanolic extract was about (2.811-3.793) mg QE/g Dw (Sadoun et al, 2021).…”
Section: Fl/pc -Fortification Factormentioning
confidence: 99%
“…In Iraq, (Sadoun et al, 2021) analyzed the flavonoid contents of the ethanolic extract of coriander which was ranged from 3.422 to 8.112 mg QE/g DW. This value is close to the present obtained results, while the methanolic extract was about (2.811-3.793) mg QE/g Dw (Sadoun et al, 2021). Other studies carried out in Morocco by (Derouich et al, 2020) demonstrated that the total flavonoids reached 10.24 mg QE/g DW in the methanolic extract of coriander.…”
Section: Fl/pc -Fortification Factormentioning
confidence: 99%
“…The using of biomass versus petroleum resources needs to determine the choice among them through the efficiency and sustainability of the production of this biomass, and this means the necessity to set priorities for the allocation of biomass, due to direct competition between food, energy, fodder and industrial raw materials in terms of price and Abundance and non-food competitiveness [1,2] , so the materials used in this research were selected on this basis after studying the extent of their competitiveness and the possibilities of their work in medical and other fields, and all of that is from extracting the raw materials for their synthesis and treatment from available materials in nature or waste [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%